Question #bce48

1 Answer
Feb 22, 2018

Parallel line, y = -x -1 or x + y = -1
Perpendicular line, y =x + 5

Explanation:

Let say m_1 is a gradient for line x + y = 7

y = -x + 7 -> m_1 = -1

since it is a parallel line, they have the same gradient value.
(y - 2) = m_1(x - (-3))
y - 2 = -1(x + 3)
y = -x -3 + 2
y = -x -1 or x + y = -1

Assuming m_2 is a gradient for the perpendicular line thru point (-3, 2), therefore

m_1 * m_2 = -1
-1 * m_2 = -1 ->m_2 = 1

for perpendicular line,
(y - 2) = m_2(x - (-3))
y - 2 = 1(x + 3)
y = x + 3 + 2
y =x + 5